Antibiofilm, Anti-Inflammatory, and Regenerative Properties of a New Stable Ozone-Gel Formulation - Carla Russo; Giuseppe Curcio; Alessandro Graziani; Antonella Mencacci; Donatella Pietrella (Pharmaceutics)
Background/Objectives: Chronic skin wounds are characterized by inflammation, persistent infections, and tissue necrosis. The presence of bacterial biofilms prolongs the inflammatory response and delays healing. Ozone is a potent antimicrobial molecule, and many formulations have been used in the advanced therapeutic treatment of chronic wounds. The aim of this work was to determine the antimicrobial, anti-inflammatory, and regenerative activity of a stable ozone-gel formulation over time. Methods: The antimicrobial property was assessed by measuring the minimal inhibitory concentration and the antibiofilm activity. The anti-inflammatory effect was evaluated by TNF-α determination, and the regenerative effect was measured by scratch assay. Results: The ozone gel demonstrated antimicrobial and antibiofilm activity in all ATCC microorganisms examined and on most clinical isolates. Higher concentrations of the ozone gel were also useful in the dispersion of preformed biofilm. The ozone gel also showed anti-inflammatory activity by reducing the production of TNF-α and regenerative activity in human fibroblasts and keratinocytes. Conclusions: Given all these antimicrobial, anti-inflammatory, and regenerative characteristics, the ozone gel could be, in this formulation, used in the treatment of wounds. The ozone-gel formulation described here retains stability for over 30 months, which facilitates its use compared to formulations that lose efficacy quickly.